Experimental investigation on enhancement of ammonia absorption process with TiO2 nanoparticles in newly designed absorber. (April 2019) - Jiang, Weixue; Li, Shuhong; Yang, Liu; Du, Kai
Highlights: A new absorber is designed for the AARS to investigate the absorption processes. Concentration of strong solution is the decisive parameter to the absorption effect. The effect of the addition of nanoparticles on the absorption effect is very obvious. 0.5% mass fraction of nanoparticles is optimal addition for absorption processes. The enhanced thermal conductivity of the nanofluid dominates the absorption process. Abstract: This paper designs a new absorber for the AARS and investigates the absorption processes with 0.1 wt%, 0.3 wt% and 0.5 wt% of TiO2 nanoparticles added to solution circle. More notably, it is not a separate absorption process, but an absorption process in a complete AARS, which is different from previous literature reports, the investigation. In the newly designed absorber, the spray absorption process and falling film absorption processes are carried out in sequence, thereby making the absorption process more thorough. The absorption performance is mainly determined by the concentration of the strong solution at different evaporation temperatures, generation temperatures, and inlet cooling water temperatures. The experimental results show that the added nanoparticles have significant effect on absorption process, which can make the temperature of the strong solution is lower, the concentration of the strong solution is higher, and the outlet cooling water temperature is higher compared with experiments without nanoparticles under the same operating conditions. More importantly, these effects are more obvious as the amount of nanoparticles added increases during the experiments. The analysis results indicate that the thermal conductivity of the nanofluids dominates the absorption process.